Exploring a Mainland Chinese Undergraduate‘s Linguistic Identity Trajectory in Hong Kong (Journal of Education and Development, 2023)
The internationalisation of higher education witnesses the increasing student mobility across borders and the emergence of more and more EMI universities worldwide, which may simultaneously offer opportunities to and pose challenges on cross-border students‘ language experiences and identities. The intra-state cross-border context of mainland Chinese students pursuing higher education in Hong Kong is a unique one, given the close ties between the two sides and Hong Kong‘s multilingual ecology. However, not enough attention seems to have been given to these students‘ linguistic experiences, especially in terms of how their linguistic identities evolve across time and space. Therefore, this case study aims to delve into the linguistic identity trajectory of a mainland Chinese undergraduate studying in Hong Kong, with specific emphasis on how and why her linguistic self-identifications might be multiple, dynamic, contesting and contextually situated. Purposefully selecting the participant, the study adopts Photo-Elicitation Interviews to elicit her narratives from visual materials. Her detailed and unique language use stories exhibit a conversion from contradictory and competing multiple linguistic identities to a core and relatively stable multilingual identity. Moreover, by identifying the contributing factors, this study argues that individuals‘ linguistic identities reside in an organic system of language ideology, power relation and community, with the complex interplay between factors contributing to the constant evolution of linguistic identities.